A Comparison of Different Design Methods for the LLC Converter with Capacitive Output Filter - Oeder, Christian; Bucher, Alexander; Stahl, Jürgen; Dürbaum, Thomas (12th IEEE Workshop on Control and Modeling for Power Electronics (COMPEL 2010), 2010)
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.acompa

Analysis and Design of a Contactless Power Transmission System Based on the Extended First Harmonic Approximation - Bucher, Alexander; Dürbaum, Thomas (IEEE Industrial Application Society (IAS) Annual Meeting, 2012)
For the task of transferring energy inductively, resonant converters are a suitable family of converters in order to overcome the technical hurdle of the loose magnetic coupling that is often encountered in this kind of application. However, the analysis of resonant converters is in general cumbersome. In order to facilitate the design process where a vast number of converter configurations has to be computed, approximations are required in order to bring the necessary computational time to maintainable levels. A design procedure for a contactless power transmission system based on the extended first harmonic approximation for the steady-state solution of the multi-resonant LLCC converter is presented in this paper, with a new degree of simplification regarding the resulting closed-form solution. By means of this approximation, the design of the fourth-order resonant LLCC converter is significantly simplified, providing a tool for rapid simulation combined with a very high accuracy. The resulting system was designed to be very tolerant against variations of the distance between the coils, at the same time achieving a very high efficiency for this kind of application. © 2012 IEEE.
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.lselek.analys_2
Keywords: Inductive power transmission; resonant converters

Analysis and Design of a LCC Converter for Low-Profile Resonant Power Adapters - Pawellek, Alexander; Bucher, Alexander; Dürbaum, Thomas (2011)
UnivIS-Import:2019-08-15:Pub.2011.tech.IE.lselek.analys

Analysis and Design of a Low-Profile Resonant LCC Converter - Pawellek, Alexander; Bucher, Alexander; Dürbaum, Thomas (Applied Power Electronics Conference (APEC), Palm Springs, USA, 2010)
In addition to high efficiency of switch mode power supplies, miniaturization of converters is an increasingly important aspect. In order to meet safety regulations as well as the design goal of flatness, complicated integrated magnetics are proposed in literature. Unfortunately, their design is difficult and the costs of these components are rather high. This paper focuses on the resonant LCC converter with capacitive output filter, which is a promising topology with respect to low-profile designs. The transformer necessary for mains isolation is realized on a ring core, thus regulation requirements are combined with a low-cost magnetic component. The exact analysis of the LCC converter in the time domain is presented and the solutions of the four important modes of the converter are derived. A prototype was designed in order to demonstrate the feasibility of the proposed approach with an application scenario typical for notebook adapters. ©2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.analys_8

Analysis and Design of a Resonant LCC Converter for Low-Profile Applications - Pawellek, Alexander; Bucher, Alexander; Dürbaum, Thomas (IEEE International Symposium on Industrial Electronics (ISIE 2010), 2010)
In addition to high efficiency of switch mode power supplies, miniaturization of converters is an increasingly impor-tant aspect. In order to meet safety regulations as well as the design goal of flatness, complicated integrated magnetics are proposed in literature. Unfortunately, their design is difficult and the costs of these components are rather high. This paper focuses on the resonant LCC converter with capacitive output filter, which is a promising topology with respect to low-profile designs. The transformer necessary for mains isolation is rea-lized on a ring core, thus regulation requirements are combined with a low-cost magnetic component. The exact analysis of the LCC converter in the time domain is presented and the solutions of the four important modes of the converter are derived. A prototype was designed in order to demonstrate the feasibility of the proposed approach with an application scenario typical for notebook adapters. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.analys_5

Characterization of a modified LISN for effective separated measurements of common mode and differential mode EMI noise - Stahl, Jürgen; Kübrich, Daniel; Bucher, Alexander; Dürbaum, Thomas (Energy Conversion Congress and Exposition (ECCE), 2010 IEEE, 2010)
The compliance with standards calls for proper designed EMI filters. EMI typically comprises common mode (cm) and differential mode (dm) noise. A systematic optimization of EMI filters requires the knowledge of the contribution and distribution of these two noise sources. The paper discusses different methods that allow the independent measurement of cm and dm noise. One suitable method described in detail integrates the separation set-up into the Line Impedance Stabilization Network (LISN). However, a correct interpretation of the measured results requires a characterization of the unavoidable modal conversion of the complete set-up - i.e. the measured level at the dm output in case of pure cm excitation and vice versa. As shown in this paper, the implementation of a standard LISN introduces a high amount of imperfections causing the undesired modal conversion. Thus, for the first time, this paper describes the characterization of the whole set-up including the LISN. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.charac_0
Keywords: Characterization of noise separation; Common mode (cm); Differential mode (dm); EMC; EMI; LISN; Noise separation

Comparison of Different PWM Converter Small-Signal Models - Bucher, Alexander; Schmid, Markus; Bendkowski, Lukas; Dürbaum, Thomas (PCIM Conference, May 2008, 2008)
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.lselek.compar

Comparison of Output Rectifier Topologies in Case of a Low-Profile LLC Converter - Oeder, Christian; Bucher, Alexander; Dürbaum, Thomas (PCIM Conference, May 2012, 2012)
Miniaturization is currently one of the most important trends within the field of power electronics. In order to achieve this goal, increased switching frequencies are desirable in order to reduce the size of passive components. Resonant converters seem to be very suitable for those applications, due to the fact that virtually no switching losses occur, making high switching frequencies together with high efficiency possible. In this paper, based on its mathematical description in the time domain, a low-profile resonant LLC converter with capacitive output filter is designed with respect to a typical notebook adaptor application. In this context, special attention is paid to a low-profile design of the magnetic component. Furthermore, three different output rectifier topologies are compared in terms of efficiency of the LLC converter. © VDE Verlag GMBH - Berlin.
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.lselek.compar

Consideration of Conduction Losses for the Series Resonant Converter by Means of a Simple Extension to the SPA Approach - Bucher, Alexander; Dürbaum, Thomas; Kübrich, Daniel; Schmid, Markus (Power Electronics and Motion Control Conference, September 2008, 2008)
The cumbersome derivation of the steady-state characteristics of resonant converters can be simplified by means of the state-plane analysis. Under the assumption of ideal components, a closed-form solution can be derived in case of the series resonant converter above the resonant frequency. However, losses due to parasitic resistances cannot be easily included within this approach. Nevertheless, a more precise prediction of the converter's output characteristics taking the conduction losses into account is desirable. Therefore this paper describes a simple extension to the regular approach that leads to better agreement with measurements. This approach is based on the results derived under ideal assumptions, thus avoiding a more complicated and tedious analysis including the conduction losses. © 2008 IEEE.
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.lselek.consid
Keywords: Modelling; Resonant converter; ZVS converter

Discrepancies Caused by Approximation Methods in Case of Resonant LLC Converters with Capacitive Output Filter - Oeder, Christian; Bucher, Alexander; Stahl, Jürgen; Dürbaum, Thomas (International Conference on Power Electronics Drives and Motion PCIM, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.discre

Extended First Harmonic Approximation in Case of LLCC Converters with Capacitive Output Filter - Bucher, Alexander; Dürbaum, Thomas (15th IEEE Mediterranean Electrotechnical Conference (MELECON), 2010)
The analysis of resonant converters is in general more cumbersome than in case of PWM converters, as often a multitude of modes has to be regarded and resonant oscillations with durations impossible to calculate directly are encountered. Therefore, approximations are required in order to facilitate the design process. An extended approximation in the frequency domain for the steady-state solution of the multi-resonant LLCC converter with capacitive output filter is presented in this paper, with a new degree of simplification regarding the resulting closed-form solution. By means of this approximation, the design of the fourth-order resonant LLCC converter is significantly simplified, providing a tool for rapid simulation combined with a very high accuracy. The accuracy of the investigated approach was double-checked by means of exact calculations. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.extend

Fast and Accurate Simulation Method for Switch-Mode Power Supplies - Schmidt, Martin; Doebroenti, M.; Bucher, Alexander; Dürbaum, Thomas (PCIM Conference, May 2010, 2010)
In order to describe the voltage and current waveforms of a switch-mode power supply (SMPS) accurately by simulation the parasitic output capacitance of the MOSFET cannot be neglected. For this reason the paper describes and compares two different simulation methods which take this capacitance into account without extending the simulation time considerably, so that a fast and accurate transient simulation of the SMPS is obtained. The first method is an analytical solution with an equivalent linear capacitance. The second method really considers the non-linear dependency of the capacitance on the voltage. The measurement at the end shows, that the second method describes the SMPS very accurately. Furthermore a comparison with a calculation which neglects the parasitic capacitance shows the relevance of the proposed method. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.fastan
Keywords: MOSFET; Simulation; SMPS

Industrie-Schaltnetzgeräte im Test Teil 3: elektromagnetische Eigenschaften - Teuber, Sven; Bucher, Alexander; Dürbaum, Thomas (Elektronik, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.indust_1

Low-Profile LLC Converter for Notebook Adapters - Oeder, Christian; Bucher, Alexander; Dürbaum, Thomas (International Conference on Power Electronics Drives and Motion PCIM, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.lowpro

Multi-Resonant LCC Converter - Comparison of Different Methods for the Steady-State Analysis - Bucher, Alexander; Dürbaum, Thomas; Kübrich, Daniel; Hoehne, Silvio (PESC Record - IEEE Annual Power Electronics Specialists Conference, 2008)
Several different approaches for the investigation of the steady-state properties of resonant converters have been published. In addition to solving the occurring equations in the time domain, which turns out to be quite cumbersome, the designer can make use of approximate approaches in the frequency domain. Two of these methods are compared to the exact solution with regard to their accuracy and mathematical complexity within this paper for the multi-resonant LCC converter with inductive output filter. Additionally, a minimized set of nonlinear equations is derived in case of the exact solution based upon the state-plane technique. ©2008 IEEE.
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.lselek.multir

Output Impedance Calculation by Means of Sampled-Data Modeling - Stahl, Jürgen; Bucher, Alexander; Dürbaum, Thomas (International Conference on Power Electronics Drives and Motion PCIM, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.output

Rapid simulation of multi-resonant LLCC converters with capacitive output filter based on an extended first harmonic approximation - Bucher, Alexander; Dürbaum, Thomas; Stahl, Jürgen (Energy Conversion Congress and Exposition (ECCE), 2010 IEEE, 2010)
In case of resonant converters, the corresponding steady-state analysis is in general more cumbersome than in case of PWM converters, as often a multitude of modes has to be regarded and resonant oscillations with durations impossible to calculate directly are encountered. Therefore, approximations are required in order to facilitate the design process. An extension to the well-known first harmonic approximation is investigated for the multi-resonant LLCC converter with capacitive output filter in this paper, revealing a new degree of simplification regarding the resulting closed-form solution. By means of this approximation, the design of the fourth-order resonant LLCC converter is significantly simplified, providing a tool for rapid simulation combined with a very high accuracy. The accuracy of the investigated approach was double-checked by means of exact calculations. The loss-breakdown on several prototypes shows a very high correspondence between prediction and measurement. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.rapids
Keywords: First harmonic approximation; LLCC; Resonant converters; Steady-state

Resonant LCC Converter for Low-Profile Applications - Pawellek, Alexander; Bucher, Alexander; Dürbaum, Thomas (15th IEEE Mediterranean Electrotechnical Conference (MELECON), 2010)
In addition to high efficiency of switch mode power supplies, miniaturization of converters is an increasingly important aspect. In order to meet safety regulations as well as the design goal of flatness, complicated integrated magnetics are proposed in literature. Unfortunately, their design is difficult and the costs of these components are rather high. This paper focuses on the resonant LCC converter with capacitive output filter, which is a promising topology with respect to low-profile designs. The transformer necessary for mains isolation is realized on a ring core, thus regulation requirements are combined with a low-cost magnetic component. The exact analysis of the LCC converter in the time domain is presented and the solutions of the four important modes of the converter are derived. A prototype was designed in order to demonstrate the feasibility of the proposed approach with an application scenario typical for notebook adapters. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.resona

Sampled-Data Modeling Applied to Output Impedance Reveals Missing Term in State-Space Averaging - Stahl, Jürgen; Bucher, Alexander; Oeder, Christian; Dürbaum, Thomas (12th IEEE Workshop on Control and Modeling for Power Electronics (COMPEL 2010), 2010)
The investigation of the stability of larger power systems requires knowledge about output impedances of switch mode power supplies (SMPSs). Methods for the prediction of this quantity of a SMPS comprise state-space averaging and sampled-data modeling. However, results obtained from both methods exhibit large differences. Furthermore, sampled-data modeling itself yields completely different results for different sampling points. Negative as well as positive incremental impedances may occur. Nevertheless, considerations of the steady-state in time domain prove the existence of these strongly different results, as discussed in this paper. In addition to that, it will be shown that only small additional effort is necessary to simulate the converter behavior with exact averaged quantities. This leads directly to an improvement of the state-space average model by means of adding an operating point dependent resistor.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.sample
Keywords: Exact averaging; Output impedance; Sampled-data modeling; State-space averaging

Simple Extension to the State-Plane Analysis Approach for the Series Resonant Converter to Include Conduction Losses - Bucher, Alexander; Dürbaum, Thomas; Kübrich, Daniel (PCIM Conference, May 2008, 2008)
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.lselek.simple

Spannungsregler kleiner Leistung im Test Teil 1: Grundlagen und Testfeld - Pawellek, Alexander; Bucher, Alexander; Dürbaum, Thomas (Elektronik, 2010)
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.spannu

Spannungsregler kleiner Leistung im Test Teil 2: Messung statischer Kenngrößen - Pawellek, Alexander; Bucher, Alexander; Dürbaum, Thomas (Elektronik, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.spannu

Spannungsregler kleiner Leistung im Test Teil 4: Dynamische Kenngrößen und elektromagnetische Verträglichkeit - Pawellek, Alexander; Bucher, Alexander; Dürbaum, Thomas (Elektronik, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.lselek.spannu_5

Validation and Comparison of different PWM Converter Small Signal Models - Bucher, Alexander; Schmid, Markus; Bendkowski, Lukas; Dürbaum, Thomas (EPE Power Electronics and Motion Control Conference, September 2008, 2008)
In order to determine which small signal model most accurately describes PWM converters, a comparison with a switched model is necessary. Due to parasitic effects the comparison with hardware measurements does not clarify this question. Therefore published small signal models based on ideal components are compared with a time domain simulation of a switched converter using the same idealization in this paper. The transfer function is determined by emulating the quadrature detector used in practical measurement set-ups. The paper shows the theoretical background, the implementation in SPICE and the comparison with traditionally found transfer functions. © 2008 IEEE.
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.lselek.valida
Keywords: Converter control; Modeling; Simulation